Investigasi Pengelolaan Sampah Berbasis Masyarakat Melalui Bank Sampah di Kota Padang - Arum Nabila; Rizki Aziz; Shinta Indah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Waste management at the community level through waste banks has been carried out involving collaboration between the local government, the community and the private sector in Padang City. This research aims to analyze the existing conditions of waste management through waste banks in Padang City. The research was carried out by means of field observations, distributing questionnaires to the community and interviews with related parties such as the managing government, namely DLH of Padang City and waste bank administrators. The results of research through distributing questionnaires show that 81% of the people of Padang City knew about the waste bank, but only 22.2% of the people actively participate in waste bank activities. This is caused by a lack of public knowledge about selecting waste according to type, waste segregation has not been carried out at the source of the waste and the role of the community in waste management to create a clean and healthy environment. On the other hand, it is also known that cooperation between DLH of Padang City, local waste bank managers, waste bank customers and also collectors or third parties has not been integrated.